Properties of sugar palm nanocellulose fibre-reinforced biopolymer composite - Rushdan, Ahmad Ilyas (2019)
The robust economic growth and rapid development as well as population growth in Malaysia have increased the amount of plastic waste generation by households, industry and trade sectors. The National Strategic Master Plan 2005 estimated that a total of 31,500 tonnes of solid wastes generated per day by 2020. To resolve the ongoing problems caused by non-biodegradable plastics, natural biopolymers which are also environmental friendly plastic have been investigated as potential alternatives to replace conventional plastic. Starch is one of the most widely available biopolymers for packaging application as well as potential alternative to non-biodegradable plastics as it is affordable, wide availability, biodegradable and renewable. The major challenges for the development of starches as packaging films are the shortcomings related to brittleness, processability, high moisture sensitivity, and poor mechanical and water barrier properties. In order to transform native sugar palm starch (SPS) into high performance thermoplastic starch for packaging application, sugar palm nanocrystalline cellulose (SPNCCs) and sugar palm nanofibrillated cellulose (SPNFCs) were extracted from sugar palm fibre (SPF) and utilized to reinforce the matrix of SPS. The SPNCCs and SPNFCs were isolated using chemical (acid hydrolysis) and mechanical (high pressurized homogenization) treatments, respectively. The characterization of SPNCCs and SPNFCs was performed using TEM, FESEM, AFM, DP, TGA, DSC, DMA, FTIR, BET, XRD, zeta potential, chemical composition, density, and moisture content. From the implemented experiment, the dimension of the obtained SPNCCs and SPNFCs was in nanometer range in the form of needle-like and thread-like particles shapes, respectively, with less aggregated in suspension and high thermal stability which was attributed to their high crystallinity and stiffness. The SPNCCs presented a high crystallinity value of 85.9%, length (L) of around 130 ± 30 nm and the average diameter (D) of 9 ± 1.96 nm with yield value of 29%. Meanwhile the SPNFCs presented a high crystallinity value of 81.2%, length (L) of around several micrometers and average diameter (D) 5.5 ± 0.99 nm with yield value of 92%. SPNCCs and SPNFCs reinforced SPS composite film were developed using solution casting method. The effects of different SPNCCs and SPNFCs concentrations (0 – 1.0 wt. %) on the physical, mechanical, biodegradability, thermal and water barrier properties of nanocomposite films were evaluated. The addition of the concentration of sugar palm nanocellulose from 0.1 to 1.0 % significantly improves the water barrier and mechanical properties of the reinforced SPS nanocomposite films compared to control SPS films. It was incredible to note that the SPNCCs reinforced SPS nanocomposite films showed an increase in Young’s modulus and tensile strength from 54 to 178.83 MPa and 4.80 to 11.47 MPa with increasing nanofillers concentration from 0 to 1.0 wt %, respectively. Whereas for SPNFCs reinforced SPS nanocomposites, the films showed an increase in Young’s modulus and tensile strength from 54 to 121.26 MPa and 4.80 to 10.68 MPa with increasing nanofillers concentration from 0 to 1.0 wt %, respectively. The addition of SPNCCs and SPNFCs within SPS nanocomposites reduced the films solubility from 33.36 % (neat film) to 14.76 % and 18.60, respectively, which proved that the films have good water stability. Moreover, sugar palm nanocellulose reinforced sugar palm starch nanocomposite was anticipated to have good interfacial adhesion to improve the water barrier and mechanical properties and biocompatibility. The development of such fully biodegradable packaging films is important in the effort to address the ongoing environmental problems and gradually substitute the widely used conventional packaging materials.